THE EFFECT OF PRENATAL EDUCATION ON NVP LEVELS - Wahyuni, Santi; Badriah, Badriah (Journal of Maternity Care and Reproductive Health, 2024)
Background: Nausea and Vomiting of Pregnancy (NVP) can affect around 70-80% of pregnant women and has an impact on reducing quality of life. Various management efforts have been made to overcome NVP, including providing prenatal education. Objective: to determine the effect of prenatal education on the severity of NVP in Cirebon Regency. Method: quasi-experimental with one group pre-posttest design. The research population was pregnant women in the working area of the Plumbon Community Health Center, Cirebon Regency who experienced NVP. The number of research respondents was 30 people, determined using a purposive sampling technique. The research instruments were a knowledge questionnaire and PUQE-24 hour index scoring. Univariate and bivariate data analysis, using parametric analysis (paired t test). Results: the majority of respondents (76.7%) had the severity of NVP before prenatal education intervention in the moderate category. After being given the intervention, there was a decrease in the severity of NVP, the level of moderate responders became 50%, and the mild level increased from 23.3% to 50%. The results of statistical tests show that prenatal education for pregnant women has a significant effect on reducing the severity of NVP with α=0.030 <0.05. Conclusion: prenatal education has an effect on reducing the severity of NVP so that it can be considered as a complementary therapy in treating NVP.